2019
DOI: 10.1055/s-0039-1694029
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Augmentation: A Systematic Review

Abstract: Clinicians employ various modalities in order to achieve temporal augmentation; however, no literature comprehensively describes these methods or provides perspective on available options. Understanding the available methodologies for cosmetic temporal augmentation allows for improved patient satisfaction with limited risk of complications. To synthesize the available literature on cosmetic temporal augmentation, including all available methodologies, patient satisfaction data, and complication rates, as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…16 In some cases, it is possible to have a postinjection headache and discomfort with mastication, which generally resolves spontaneously within 24 to 48 hours. 17…”
Section: Temporal Regionmentioning
confidence: 99%
“…16 In some cases, it is possible to have a postinjection headache and discomfort with mastication, which generally resolves spontaneously within 24 to 48 hours. 17…”
Section: Temporal Regionmentioning
confidence: 99%
“…A variety of secondary strategies to address temporal hollow have been described, and include injectable fillers, fat grafting, botox, or solid implants. [14][15][16][17][18][19] Prevention of postoperative caudal temporalis descent necessitates stable adherence of the muscle to its intraoperative suspended position. Experience has shown that the muscle will not reliably adhere to PEEK, resulting in caudal descent of the muscle.…”
Section: Soft Tissue Managementmentioning
confidence: 99%
“…At this time, one can palpate the frontal branch of the superficial temporal artery at the level superior or inferior to the horizontal line of the superior orbital rim running toward the midline of the face above the brow. 4 The treating practitioner should ensure proper illumination and magnification to achieve the desired result. Once injected, the cannula is quickly fanned throughout the temporal region to evenly distribute the product throughout the potential space needing volume.…”
Section: Injection Techniquementioning
confidence: 99%